2020
DOI: 10.1002/ece3.7018
|View full text |Cite
|
Sign up to set email alerts
|

Innate preference hierarchies coupled with adult experience, rather than larval imprinting or transgenerational acclimation, determine host plant use in Pieris rapae

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Experience during the juvenile stage can affect adult behavior and host selection [74]. A number of studies with Helicoverpa armigera and Spodoptera littoralis suggest larval experience of host plants can affect host plant choice in adults, with the plant experienced during the immature stage being favored in female oviposition [75][76][77][78] but this is not always the case [79][80][81][82]. Since in our experiment the change in preference towards the initially non-preferred plant took at least 4 generation it suggests selection, but we cannot rule out gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Experience during the juvenile stage can affect adult behavior and host selection [74]. A number of studies with Helicoverpa armigera and Spodoptera littoralis suggest larval experience of host plants can affect host plant choice in adults, with the plant experienced during the immature stage being favored in female oviposition [75][76][77][78] but this is not always the case [79][80][81][82]. Since in our experiment the change in preference towards the initially non-preferred plant took at least 4 generation it suggests selection, but we cannot rule out gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…pupal weight and wing size) when parent and offspring diets match . However, in another study, P. rapae, were unable to transgenerationally acclimatize its offspring when parent and offspring were reared on similar plant species (Petrén et al 2021). This could infer that different populations of insects react differently, or that transgenerational acclimatization could act on within-species variation in terms of nutrition.…”
Section: Transgenerational Phenotypic Plasticitymentioning
confidence: 97%
“…In insects, with an emphasis on Lepidopterans, it has been suggested that their ability to express WGP should favour TGP . In herbivorous insects, specifically in individuals that use WGP for host-plant choice, the increased chance of a matching parentoffspring environment could favour the ability to transgenerationally acclimatize the offspring to the environment experienced by the parent Petrén et al 2021). This would link the two types of plasticity, emphasising the importance of WGP for TGP .…”
Section: Behavioural Plasticity As a Facilitator For Transgenerationa...mentioning
confidence: 99%